Hubungan Asupan Lemak Dan Indeks Massa Tubuh Dengan Tekanan Darah Pada Lansia Di Posyandu Lansia Desa Bolon Kecamatan Colomadu Kabupaten Karanganyar - Sulistia Dewi, Eka Yuniar (2017)
Introduction : Intake of excessive eating can lead to obesity, such as the accumulation of fat. The increase in body mass index (BMI) is a major risk factor for several types of cancer, diabetes, osteoarthritis and high blood pressure potential that will lead to heart disease and stroke. Fat consumption habits closely associated with weight gain risk of an increase in blood pressure. One of the health problems that often occur in the elderly or the elderly is hypertension or high blood pressure. Objective : Knowing the relationship of fat intake and body mass index at blood pressure in the elderly in posyandu lansia Desa Bolon Kecamatan Colomadu Kabupaten Karanganyar. Research Method : This research used Cross Sectional Design. The number of this research respondents are 49 people using simple random sampling method. Fat intake data were obtained by using Food Frequency Quesionnaire during the last month. Weight measurement data by using bathroom scales, while the height measurement by using microtoa, and the measurement of systolic and diastolic blood plasure using sphygnomanometer tool which is done by health worker that is nurse or doctor. Test data relationship that are normally distributed using Pearson Product Moment test and abnormal data using Rang Spearman test. Result : The results showed that the most fat intake was normal fat intake with saturated fat 60%. Body mass index is most overweight 38,8% and obesity 30,6%, and systolic blood pressure measurements were higher by 55,1%, while the diastolic blood pressure higher by 61,2%. The result of the relationship of fat intake with systolic blood pressure value p value >0,05 (p 0,922) and diastolic value p value >0,05 (p 0,146). While the correlation of test results with a body mass index of systolic blood pressure value p value <0,05 (p 0,028) and diastolic value p value <0,05 (p 0,023). Conclusion : There is no relationship of fat intake with systolic and diastolic blood pressure in the elderly. There is a relationship with a body mass index of systolic and diastolic blood pressure in the elderly in the posyandu lansia Desa Bolon Kecamatan Colomadu Kabupaten Karanganyar. Keyword : Fat Intake, Body mass index, Blood Pressure